2010
DOI: 10.1261/rna.1851510
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of microRNA stability

Abstract: MicroRNAs (miRNAs) are endogenous single-stranded RNA molecules of about 21 nucleotides in length that are fundamental post-transcriptional regulators of gene expression. Although the transcriptional and processing events involved in the generation of miRNAs have been extensively studied, very little is known pertaining to components that regulate the stability of individual miRNAs. All RNAs have distinct inherent half-lives that dictate their level of accumulation and miRNAs would be expected to follow a simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
257
1
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 270 publications
(280 citation statements)
references
References 39 publications
(46 reference statements)
16
257
1
4
Order By: Relevance
“…HEK293T cells were transfected by pLKO.1-shXRN1 (Sigma #TRCN0000049676) or pLKO.1-shRRp41 (Sigma #TRCN0000051365), and pCMV-VSVG and psPAX2 with Lipofectamin2000 (Life Technologies) to generate viral particles. Culture medium was harvested two days post-transfection and frozen at −80°C for storage (Bail et al 2010). …”
Section: Plasmid Constructsmentioning
confidence: 99%
“…HEK293T cells were transfected by pLKO.1-shXRN1 (Sigma #TRCN0000049676) or pLKO.1-shRRp41 (Sigma #TRCN0000051365), and pCMV-VSVG and psPAX2 with Lipofectamin2000 (Life Technologies) to generate viral particles. Culture medium was harvested two days post-transfection and frozen at −80°C for storage (Bail et al 2010). …”
Section: Plasmid Constructsmentioning
confidence: 99%
“…A target-dependent mechanism has also been identified, in which turnover is mediated by the interaction of miRNAs with their mRNA targets, promoting miRNA unloading from AGO and degradation (Baccarini et al 2011;Ruegger and Grosshans 2012;De et al 2013;de la Mata et al 2015). One main reason for this lack of knowledge is the lack of experimental approaches that allow the analysis of miRNA half-lives at the global level without perturbing gene transcription or miRNA biogenesis (Bail et al 2010;Gantier et al 2011;Guo et al 2015). To overcome such issues, we exploited metabolic pulse labeling, the gold standard method used to determine RNA and protein halflives, and developed a "pulse-chase" approach optimized for the analysis of miRNAs.…”
mentioning
confidence: 99%
“…In 2010, we reported that miR-27 is rapidly down-regulated in mouse cells infected with murine cytomegalovirus (MCMV), resulting in >90% reduction by 24 hours post-infection. 17 This observation was intriguing because the half-lives of most miRNAs are reported to be in the range of days 18 . We and others subsequently identified an MCMV transcript that directly associates with mature miR-27 and mediates its degradation.…”
Section: Introductionmentioning
confidence: 99%